Research and optimization on the strength recovery mechanism of post peak fragmentation grouting reinforcement in mining rock mass - Shuai, Zhang; Yao, Sun; Jiantao, Cao; Xingping, Lai; Longquan, Wu (Frontiers in Materials, 2025)
To reveal the strength recovery characteristics of grout-reinforced engineering rock masses, this study is based on the small coal pillar god-side entry of the Maiduo Mountain Coal Mine. Uniaxial compression tests were conducted on grout-consolidated samples, complete surrounding rock samples, and grout-reinforced samples of post-peak broken surrounding rock. The mechanical properties of grout-consolidated samples of four grouting materials, as well as the strength recovery characteristics, crack propagation, and energy evolution of grout-reinforced post-peak fractured rock samples with different consolidation times were investigated. The results show that, compared to samples reinforced with ordinary cement, fly ash cement, and portland cement, the grout-consolidated samples made with high-performance cement-based materials exhibit the best strength recovery effect at any consolidation time, without significant pressure release or fluctuation during compression. Compared to the initial complete rock samples, the stress, strain, ring count, and cumulative energy of grout-reinforced post-peak fractured rock samples are significantly reduced, and they exhibit a notable linear positive correlation with consolidation time.